Analysis of controversies and cognitive conflicts through a lakatosian view. An application in angular kinematics learning - Carlos Eduardo Laburú (Investigações em Ensino de Ciências, 2003)
This work proposes to observe the students’ thought construction in class in situation of stimulated cognitive conflicts and controversies. For this, we suggest using an analytic-pedagogic instrument based on an interpretation of Lakatos’s research programs. The idea is to apply this approach to qualify the students’ thought and structure these as programs. Afterwards, we apply the Posner et al. conditions to understand why student thinking is compromised with the programs.